Software engineering - Sommerville, Ian (Boston : Pearson, 2011)
This book discusses a comprehensive spectrum of software engineering techniques and shows how they can be applied in practical software projects. This edition features updated chapters on critical systems, project management and software requirements.
lntroduction to software engineering -- Dependability and security -- Advanced software engineering -- Software management.
Sisältää hakemistoja.
Keywords: data protection; software engineering; systems engineering; programming; software development; programming languages; Software -- Management; Systems engineering; Reliability; Security; Software engineering; ohjelmistokehitys; tietokoneohjelmat; ohjelmistotuotanto; ohjelmistotekniikka; ohjelmointi; ohjelmointikielet; olio-ohjelmointi.; tietotekniikka; tietojärjestelmät; testaus; projektit; tietoturva; systeemityö; programutveckling; programvaruproduktion; programteknik; programmering; datorprogram